Exploring protein myristoylation in Toxoplasma gondii - Alonso, Andrés Mariano (2019)
Toxoplasma gondii is an important human and veterinary pathogen and the causative agent of toxoplasmosis, a potentially severe disease especially in immunocompromised or congenitally infected humans. Current therapeutic compounds are not well-tolerated, present increasing resistance, limited efficacy and require long periods of treatment. On this context, searching for new therapeutic targets is crucial to drug discovery. In this sense, recent works suggest that N-myristoyltransferase (NMT), the enzyme responsible for protein myristoylation that is essential in some parasites, could be the target of new anti-parasitic compounds. However, up to date there is no information on NMT and the extent of this modification in T. gondii. In this work, we decided to explore T. gondii genome in search of elements related with the N-myristoylation process. By a bioinformatics approach it was possible to identify a putative T. gondii NMT (TgNMT). This enzyme that is homologous to other parasitic NMTs, presents activity in vitro, is expressed in both intra- and extracellular parasites and interacts with predicted TgNMT substrates. Additionally, NMT activity seems to be important for the lytic cycle of Toxoplasma gondii. In parallel, an in silico myristoylome predicts 157 proteins to be affected by this modification. Myristoylated proteins would be affecting several metabolic functions with some of them being critical for the life cycle of this parasite. Together, these data indicate that TgNMT could be an interesting target of intervention for the treatment of toxoplasmosis.